Forensic characteristics of exceeding authority or ofﬁcial powers by a military ofﬁcial, committed under martial law or in a combat situation - I. Kostiuk; I. Yefimenko (Юридичний часопис Національної академії внутрішніх справ, 2025)
The relevance of the subject matter under investigation was due to the need to improve the methodology for investigating criminal offences committed by military personnel in armed conflict. This will contribute to the establishment of the rule of law by adhering to the norms of national legislation and international legal standards for conducting hostilities and ensuring the protection of the civilian population during armed conflict. The aim of the study was to form a comprehensive forensic characteristic of military personnel exceeding their authority or official powers in order to develop effective and efficient mechanisms for their investigation. The methodological toolkit of the study encompassed a complex of general scientific and special methods that ensured a comprehensive study of the causes and conditions of military personnel exceeding their authority and official powers, and also contributed to the formation of scientifically sound approaches to their investigation, including: the comparative legal method for analysing legislative norms regulating legal relations in the military sphere; the formal-logical method for clarifying legal definitions on the research topic; the context analysis method for systematic processing of scientific approaches to investigating military offences, and also the inductive method for generalising the obtained results. The main elements of the forensic characteristic of the investigated criminal offence have been identified and analysed. These elements are divided into general and special, or contextual. They include: the place, time, and period of commission the unlawful acts, the identity of the offender, the purpose, motives, and conditions that contributed to the commission of the criminal offence, the methods of implementing criminal acts (intentions), the identity of the victim, the socially dangerous consequences of the offence, the degree of their danger, and also the connection of the investigated criminal offence with actions that imply a different criminal legal qualification or exclude criminal liability for the committed act. The scientific significance of the obtained results lies in the improvement of the f ve as a basis for creating methodological guidelines for investigating these types of criminal offences